Annexin A2 autoantibodies in thrombosis and autoimmune diseases (2015)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by arterial, venous or small-vessel thrombotic events, and recurrent miscarriages or fetal loss. APS diagnosis is based on the repeated detection of anti-phospholipid (PL) antibodies (Ab), typically associated with anti-beta 2 glycoproteinI (beta 2GPI)-Ab. Recent studies suggest that anti-beta 2GPI Ab activity involves a protein complex including beta 2GPI and annexin A2 (ANXA2). Anti-ANXA2 Ab recognizes this complex, and these Ab can effectively promote thrombosis by inhibiting plasmin generation, and by activating endothelial cells. Therefore, anti-ANXA2 Ab represent a new biomarker, which can be detected in up to 25% of APS patients. Moreover, anti-ANXA2 Ab have been detected, in thrombotic associated diseases including pre-eclampsia, in other autoimmune diseases, and in cancer. (C) 2014 Elsevier Ltd. All rights reserved.